Overlap of isochrone resonances: Chaos and refraction - Egydio de Carvalho, R. [UNESP] (American Physical Society (APS), 1997)
We consider the two nonconcentric circles billiard, with the inner circle as a refringent medium, in order to study the classical dynamics of a light ray. The eccentricity controls the chaotic sea intensity and the refraction index acts on the integrable portion of the phase space, prompting the appearance and overlapping of isochrone resonances. Numerical results are presented and discussed.